Ameliorated effects of a lipopeptide surfactin on insulin resistance in vitro and in vivo. Issue 7 (29th March 2022) - Chen, Xiaoyu; Zhao, Hongyuan; Meng, Fanqiang; Zhou, Libang; Pang, Xinyi; Lu, Zhaoxin; Lu, Yingjian
Abstract: Surfactin, produced by Bacillus amyloliquefaciens fmb50, was used to treat insulin‐resistant (IR) hepatocyte. It was found that surfactin increased glucose consumption in insulin‐resistant HepG2 (IR‐HepG2) cells and ameliorated IR by increasing glucose transporter 4 (GLUT4) protein expression and AMP‐activated protein kinase (AMPK) mRNA expression, promoting GLUT4 translocation and activating phosphatidylinositol 3‐kinase (PI3K)/protein kinase B (Akt) in IR‐HepG2 cells. Meanwhile, surfactin downregulated protein expression of phosphoenolpyruvate carboxy kinase (PEPCK) and glucose‐6‐phosphatase (G6Pase), further inhibiting hepatic gluconeogenesis. In addition, surfactin played important roles in eliminating reactive oxygen species (ROS), improving mitochondrial dysfunction, and inhibiting proinflammatory mediators. We observed that surfactin promoted glucose consumption, meanwhile increased translocation and protein expression of GLUT4 in Caco‐2 cells. These results confirmed the conclusion in hepatic cells. Furthermore, surfactin supplement decreased body weight, food intake, and fasting blood glucose of type 2 diabetes mellitus (T2DM) mice induced by streptozotocin (STZ)/high‐fat diet (HFD). Our data indicated that surfactin ameliorated insulin resistance and lowered blood glucose in intro and in vivo. Abstract : Surfactin ameliorated IR by inhibiting gluconeogenesis, oxidative stress, mitochondrial damage, and proinflammatory factors in HepG2 cells, meanwhile promoted glucose consumption by increasing protein expression and translocation of GLUT4 in Caco‐2 cells. In addition, surfactin also ameliorated T2DM through lowering body weight, food intake, and fasting blood glucose mice induced by STZ/HFD.